Stress Levels, Hyperglycemia, and Long Suffering from Diabetes Relationship with Diabetic Neuropathy Pain - Lase, Wahyu Ningsih; Laoli, Hadirat Candra (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Diabetes mellitus often causes death in sufferers, making prevention and treatment are necessary to address its various chronic issues. This study examines the relationship between stress levels, hyperglycemia, and long suffering from diabetes with diabetic neuropathy pain. It employs a correlational analysis using a cross sectional design conducted between August 2023 and 2024. The population was all diabetes mellitus patients in the UPTD area of the North Gunungsitoli Health Centerw with a sample of 103 individuals selected through proportional stratified random sampling. The research instrument was a questionnaire covering each independent and dependent variable: stress level (15 items), hyperglycemia (15 items), long-term diabetes (10 items), and neuropathy pain (10 items). Data collection included both primary and secondary data from respondents and the Gunungsitoli City Office. The data were analyzed using univariate, bivariate, and multivariate tests, with bivariate analysis conducted using spearman rank correlation and multivariate analysis using logistic regression. The results indicated a positive and significant relationship between independent and the dependent variable, with values for stress levels (p=0.000), hyperglycemia (p=0.003), and long suffering from diabetes (p=0.002). Thus, it can be concluded that the knowledge and awareness of people with diabetes mellitus are crucial for their ability to engage in healthy physical activity, regulate their diet, consistently take medication, and manage blood glucose levels.